The Power of Short Video Content on TikTok Shop Consumers in Viet Nam - NGUYEN THI PHUONG, Giang; THAI DONG, Tan; NGUYEN BINH PHUONG, Duy; TRAN VU QUYNH, Nhu; TRUONG THANH, Ngan; NGUYEN THI, Lien; NGUYEN NGOC THAO, Phuong (Theoretical and Practical Research in Economic Fields; Vol 16 No 2 (2025): TPREF, Volume XVI, Issue 2(34), Summer 2025DO - 10.14505/tpref.v16.2(34).11, 2025)
This study focuses on exploring how short-form video content on TikTok Shop goes beyond being a mere promotional tool, to become a powerful catalyst for consumer shopping behavior in Ho Chi Minh City. By surveying 766 consumers using a questionnaire refined from previous studies, the study sheds light on the factors that positively impact shopping decisions, including engagement, information, entertainment, trustworthiness, and usefulness. The collected data is analyzed through three main steps: descriptive statistical analysis, measurement model evaluation and structural model validation via SMARTPLS-3 software and SPSS 27 additional support software. The results show that short video content has the ability to increase the perceived value of consumers, significantly affecting purchase intentions and behaviors on this platform. From the above findings, the study not only helps to identify the core factors that impact purchase behavior but also proposes specific strategies to optimize video content and improve online business efficiency. Therefore, the research brings practical contributions to businesses doing business on TikTok Shop and other social media platforms in improving user experience and increasing commercial value.